2021
DOI: 10.5847/wjem.j.1920-8642.2021.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Left-sided vagus nerve stimulation improves cardiopulmonary resuscitation outcomes in rats as effectively as right-sided vagus nerve stimulation

Abstract: BACKGROUND: Our group previously reported that right-sided vagus nerve stimulation (RVNS) signifi cantly improved outcomes after cardiopulmonary resuscitation (CPR) in a rat model of cardiac arrest (CA). However, whether left-sided vagus nerve stimulation (LVNS) could achieve the same eff ect as RVNS in CPR outcomes remains unknown.METHODS: A rat model of CA was established using modified percutaneous epicardial electrical stimulation to induce ventricular fi brillation (VF). Rats were treated with LVNS or RVN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…In our study, we chose to stimulate the left cervical vagus nerve due to its lesser impact on heart rate and its preference among clinical patients 49 . This is despite evidence suggesting that stimulation of either the left or right side yields similar improvements in cardiopulmonary resuscitation (CPR) outcomes in rats 50 . Researchers have discovered that mesenchymal stromal cells (MSCs) can induce lung protection by activating the vagal anti‐inflammatory pathway, as evidenced by the detection of Ach in the BALF 47 …”
Section: Discussionmentioning
confidence: 99%
“…In our study, we chose to stimulate the left cervical vagus nerve due to its lesser impact on heart rate and its preference among clinical patients 49 . This is despite evidence suggesting that stimulation of either the left or right side yields similar improvements in cardiopulmonary resuscitation (CPR) outcomes in rats 50 . Researchers have discovered that mesenchymal stromal cells (MSCs) can induce lung protection by activating the vagal anti‐inflammatory pathway, as evidenced by the detection of Ach in the BALF 47 …”
Section: Discussionmentioning
confidence: 99%
“…This result is consistent with a previous study by Sun et al, 2017, who demonstrated that after 8 min of ventricular fibrillation (VF) CA in rats, right cervical VNS initiated for 4 h at the beginning of chest compression with 10% reduction in HR, improved cerebral function, and 72 h survival (Sun et al, 2018 ). While pre-treatment studies present a range of difficulties, nevertheless, Shao et al demonstrated that 30 min of VNS to right or left cervical vagus nerve before inducing VF in rats significantly improved 72 h survival (Shao et al, 2021 ), suggesting that stimulation of either cervical vagus nerve can confer a protective effect. Thus, to activate the array of cervical vagus nerve fibers (afferent and efferent) and achieve optimal effect (Ahmed et al, 2021 ; Chang et al, 2020 ), we applied electrical tVNS after 12 min CA and resuscitation, and observed a substantial survival benefit as compared to control (87.5% v 37.5%, respectively; P < 0.05; Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The threshold chosen for effective left cervical VNS was a 15–20% reduction of basal HR for stimulating maximal cervical vagus nerve fibers (afferent and efferent) and getting an optimal effect (Ahmed et al, 2021 ; Chang et al, 2020 ). Various studies have used different settings to stimulate either right or left cervical vagus nerve for survival and neuroprotection (Kim et al, 2019 ; Sun et al, 2018 ; Shao et al, 2021 ), preventing cardiac damage (Xue et al, 2017 ) and protecting kidney injury (Inoue et al, 2016 ). These studies suggest that VNS may have differential effects with different stimulation parameters.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations